Differential approach to the choice of therapeutic method for patients with ovary endometriosis - M. B. Tairova; A. I. Davydov (Лечащий Врач)
Efficiency and long-term results of sclerotherapy of ovary endometriosis were studied; conditions and indications for minimal invasive intervention were grounded.